POPULATION FLUCTUATION OF Bemisia tabaci IN Capsicum chinense THROUGH APPLICATIONS OF Cordyceps fumosorosea UNDER GREENHOUSE AND OPEN-FIELD CONDITIONS - Pinto Gonzalez, Omar; Chan Cupul, Wilberth; Mendoza Arceo, Andrea (Chilean Journal of Agricultural & Animal Sciences, 2025)
Bemisia tabaci is the main insect pest affecting Capsicum chinense production worldwide. Although Cordyceps fumosorosea has demonstrated efficacy against multiple insect pests under in vitro and in vivo conditions, further in situ evaluations are required to determine its effectiveness in real-world environments. The objective of this study was to evaluate the population fluctuation of B. tabaci in C. chinense cultivation under greenhouse and open-field conditions through the application of C. fumosorosea (Cf) as a biological control agent. A factorial experimental design A×B was used, where factor A corresponded to the site (greenhouse or open-field) and factor B to the application of Cf conidiospores (with or without application). Four treatments were established: T1) greenhouse + application of Cf; T2) greenhouse without application of Cf; T3) open-field + application of Cf; and T4) open-field without application of Cf. Response variables were population fluctuation (PF), efficacy, and the area under the population progress curve (AUPPC) in adults and nymphs. A multifactorial analysis of variance (ANOVA) followed by Tukey’s test was used to analyze the response variables. A greater fluctuation of adults and nymphs was found in the open-field; however, from 56 DAT, the greenhouse crop showed greater fluctuation. The efficacy of Cf in adults was greater in the greenhouse (52.4%) than in the open-field (27.2%). The same effectiveness was found in nymphs in both the open-field (64.6%) and greenhouse (62.7%). AUPPC showed that the use of Cf, under both greenhouse and open-field conditions, helped maintain low population levels of B. tabaci nymphs and adults. Overall, the application of Cf effectively suppressed B. tabaci population fluctuations in habanero pepper, highlighting its potential for its integration into sustainable management strategies against B. tabaci.